The Application of Artificial Intelligence in English Language Teaching: Relationship between Knowledge, Attitude, and Practices among Filipino English as Second Language Teachers - Cabato, Julie Uy (2025)
This study examines the integration, potential, and implications of ChatGPT, an artificial intelligence, AI-powered chatbot, in the education field, with a particular focus on language instruction among Filipino English language teachers. As a groundbreaking example of generative AI, ChatGPT has sparked several controversies, particularly within academic communities where it is increasingly being utilized. This paper examines how ChatGPT could serve as a valuable tool for enhancing engagement and optimizing learning outcomes in educational settings, and for this study, in language instruction among Filipino English language teachers. A pilot test was conducted with 50 English language teachers to validate the investigation's instrument, ensuring their suitability for the main study. The main study involved 181 public school teachers from Zamboanga City, located in southern Philippines. The 181 respondents are drawn from a target population of 340 tenured secondary public school English language teachers. The validation and pilot testing process not only reinforced the instrument’s suitability but also provided a solid foundation for its application in the main study. The investigation addresses seven research questions, which includes three descriptive queries and four inferential questions accompanied by corresponding hypotheses. A descriptive-quantitative correlational research design is used, and the investigation employs a 39-item questionnaire to gather data. The findings reveal that many teachers possess a moderate level of familiarity with ChatGPT's basic functions; their attitudes toward the tool are largely positive. Usage patterns, however, varied significantly among respondents. Gender differences in knowledge, attitudes, and usage are found to be minimal. Notably, a moderate, statistically significant relationship was found between teachers’ knowledge of ChatGPT and their level of usage. Finally, the investigation discusses the implications of these findings and offers recommendations for integrating ChatGPT within the educational environment.